Pengaruh Der (Debt To Equity Ratio) Dan Return On Equity Terhadap Earning Per Share (Studi Kasus PT Campina Ice Cream Tbk) - Afriani, Ade; Muti, Ahmad; Rochim, Abdul (Journal of Student Development Informatics Management (JoSDIM), 2023)
This study aims to determine the effect of Debt to Equity Ratio (DER) and Return On Equity on Earning Per Share at the Campina Ice Cream Tbk company From 2017 to 2021. This study uses a quantitative method with a descriptive Approach. The data testing technique used is to test the classical assumptions. This Study uses multiple linear regression analysis and hypothesis testing. The analytical Tool used is the SPSS type 26 program. DER (Debt to Equity Ratio) is a reflection Of the company’s ability to fulfill all its obligations. The lower the DER ratio, the Higher the company’s ability to fulfill all its obligations. ROE (Return On Equity) Is a measure made to determine the ability of a company to generate profits for People who buy its shares. EPS (Earnings Per Share) is the company’s net profit Divided by the number of shares outstanding.